2022
DOI: 10.3389/fonc.2022.912246
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Serum Exosomal CircRNAs hsa_circ_0001492, hsa_circ_0001439, and hsa_circ_0000896 as Diagnostic Biomarkers for Lung Adenocarcinoma

Abstract: BackgroundCircular RNAs (circRNAs) play an important role in tumorigenesis and several circulating circRNA signatures are closely associated with tumor diagnosis. However, the expression and clinical significance of the two forms of circulating circRNAs, serum and serum exosomal, in patients with lung adenocarcinoma (LUAD), have not been characterized.MethodsThree differentially expressed exosomal circRNAs, hsa_circ_0001492, hsa_circ_0001439, and hsa_circ_0000896, were selected based on previous exosomal circR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Hence, serum EV circRNAs demonstrated consistency with the rising trend observed in serum and proved to be more effective biomarkers than serum circRNAs. This is in line with the findings of Kang et al ( 2022 ), who reported that the diagnostic sensitivity and specificity of serum EV circRNAs were higher than those of serum circRNAs, suggesting the potential of serum EV circRNAs as a more effective biomarker for lung cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, serum EV circRNAs demonstrated consistency with the rising trend observed in serum and proved to be more effective biomarkers than serum circRNAs. This is in line with the findings of Kang et al ( 2022 ), who reported that the diagnostic sensitivity and specificity of serum EV circRNAs were higher than those of serum circRNAs, suggesting the potential of serum EV circRNAs as a more effective biomarker for lung cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Forty-one articles including 68 studies were included. Of these, 28 articles on microRNAs ( 16 – 43 ), comprising 45 studies; 8 articles on lncRNAs ( 44 51 ), comprising 9 studies; and 5 articles on circRNAs ( 52 56 ), comprising 14 studies. Diagnostic effect data included TP, FP, FN, TN, Sen, Spe, AUC, diagnostic likelihood ratio positive(DLR+), diagnostic likelihood ratio negative(DLR-), and diagnostic OR(DOR).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that exosomes are rich in circRNAs, and exosomal circRNAs play a vital function in tumor biology 29 . In LUAD, Kang et al suggested that serum exosomal hsa_circ_0001492, hsa_circ_0001439, and hsa_circ_0000896 might act as the biomarkers for LUAD diagnosis 30 . Moreover, exosomal circRNA has been found to influence cancer progression by altering macrophage polarization, such as circ_0017252 31 and circFARSA 32 .…”
Section: Discussionmentioning
confidence: 99%
“… 29 In LUAD, Kang et al suggested that serum exosomal hsa_circ_0001492, hsa_circ_0001439, and hsa_circ_0000896 might act as the biomarkers for LUAD diagnosis. 30 Moreover, exosomal circRNA has been found to influence cancer progression by altering macrophage polarization, such as circ_0017252 31 and circFARSA. 32 In this, we detected high expression of circ_0001715 in the exosomes extracted from LUAD cells.…”
Section: Discussionmentioning
confidence: 99%